AN EX POST FACTO STUDY ON DISASTER PREVENTION AND RISK REDUCTION EDUCATION IMPLEMENTATION IN SPECIAL EDUCATION SCHOOLS IN INDONESIA - Cabatay, Mulina Madlangbayan; Pujaningsih, Pujaningsih (Sanata Dharma University Yogyakarta, 2025)
Indonesia is taking proactive steps to enhance disaster resilience and safeguard its citizens through the implementation of the Satuan Pendidikan Aman Bencana (SPAB). However, in disaster contexts, children with special needs and disabilities (SEND) are frequently overlooked. To further improve SPAB implementation, this research aims to investigate the cause-and-effect relationships between the compliance-based status of disaster prevention and risk reduction education in special education schools, the challenges teachers face, and the strategies employed in teaching disaster education to children with special needs and disabilities. The study employed ex post facto research design to investigate the cause-and-effect relationships between variables. Data from interviews and brief surveys were analysed using the phi coefficient, a nonparametric tool that assesses the strength and direction of correlations between variables. The researchers collected information from twenty-three special education teachers, and thirteen school principals and public relations officers across twelve special education schools in the Special Region of Yogyakarta. The results suggest that compliance-based implementation has an inverse effect on the main challenges that teachers encounter. As the quality of compliance with the specific provisions in SPAB increases, the barriers to teaching disaster education among students with special needs and disabilities decrease. However, it is important to consider that not all challenges that emerged during the implementation of disaster education were influenced by mere compliance with the SPAB provisions.